If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21x + -3 = 0 Reorder the terms: -3 + 21x = 0 Solving -3 + 21x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 21x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 21x = 0 + 3 21x = 0 + 3 Combine like terms: 0 + 3 = 3 21x = 3 Divide each side by '21'. x = 0.1428571429 Simplifying x = 0.1428571429
| 11x-15=6+10x | | 46=2x-5x+10 | | 2/3(12)-5=(12)/4 | | 4(x+4)=6x+26 | | 4(6+8+x)= | | -7+7x=-1+7x | | -83+4x=8x+21 | | -2/-1.3 | | j=0+9 | | y=-16t^2+20t+120 | | 3x/4=-2/3 | | 1/4•3 | | -90-3x=-8x+30 | | 168=-v+62 | | 10h+3p= | | 24+12y-36x=O | | 3/5x-5/2=3/4x | | 4x-129=40-9x | | 6y+20=8x-10 | | 5e^7x-5=6 | | 2(X-3)+3x=26 | | 7+a=35 | | 11x-72=108-x | | 5(3x+1)-3(x-2)=10+5x | | 3+3y=2x-15 | | 16t^2+555=0 | | P-1/4•3=-5/6 | | -6x-80=9x+130 | | 8[x+5]=7[x+8] | | 6*(4*9-10)-6= | | 10=6x-x^2 | | -6x+80=9x+130 |